2018
DOI: 10.1029/2018wr024042
|View full text |Cite
|
Sign up to set email alerts
|

New Semi‐Analytical Insights Into Stress‐Dependent Spontaneous Imbibition and Oil Recovery in Naturally Fractured Carbonate Reservoirs

Abstract: Fluid injection and withdrawal in a porous medium create changes in pore pressure that alter effective stresses within the medium. This leads to pore volume changes, which can be described by the poroelastic theory. These changes in pore volume can influence fluid flow processes, such as capillary diffusion and imbibition, potentially altering multiphase flow characteristics in subsurface reservoirs with a focus on oil recovery in the naturally fractured carbonate reservoirs. In this study, a semi‐analytical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
(79 reference statements)
0
10
0
Order By: Relevance
“…In applying equation , the dimensionless pore structure function (Γ), which is a function of tortuosity, pore size distribution, and cementation should be constant. Haghi, Chalaturnyk, and Geiger () assumed Γ to be fixed while applying effective stress in modeling carbonate rock under the assumption that a bundle of capillary tube represents the porous media. However, this study shows that in the case of sandstones, at least, rock tortuosity varies with effective stress (equation ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In applying equation , the dimensionless pore structure function (Γ), which is a function of tortuosity, pore size distribution, and cementation should be constant. Haghi, Chalaturnyk, and Geiger () assumed Γ to be fixed while applying effective stress in modeling carbonate rock under the assumption that a bundle of capillary tube represents the porous media. However, this study shows that in the case of sandstones, at least, rock tortuosity varies with effective stress (equation ).…”
Section: Discussionmentioning
confidence: 99%
“…Much more rapid human induced‐changes arise due to injection and production operations in almost all petroleum/geothermal reservoirs and CO 2 storage formations (Haghi, Kharrat, & Asef, ). Changes in effective stress leads to shape and size alterations among pores within porous media, directly impacting both intrinsic rock properties such as porosity and absolute permeability (Geertsma, ; Iglauer et al, ; Morris et al, ; Schutjens et al, ; Zhu & Wong, ; Zimmerman et al, ) and multiphase flow properties including capillary pressure and relative permeability curves (Haghi, Chalaturnyk, & Geiger, ; Haghi et al, ; Li et al, ). These flow properties are essential for describing multiphase flow in porous media, and slight changes in them can induce a significant effect on the reserve and recovery of oil and gas fields and geothermal reservoirs (Ahmed & McKinney, ), transport of contaminating nonaqueous liquid phase in aquifers (Pak et al, ), performance of CO 2 subsurface sequestration (Szulczewski et al, ), and rain water infiltration into the ground (Cueto‐Felgueroso & Juanes, ).…”
Section: Introductionmentioning
confidence: 99%
“…An accurate characterization of mechanical pore deformation, multiphase fluid transport, and their physical interactions (i.e., poromechanical interactions) in earth materials is essential for a diverse range of applications such as groundwater hydrology in the vadose zone 1 , 2 , geological CO 2 sequestration 3 , 4 , transport of non-aqueous phase liquid contaminant in aquifers 5 , 6 , extraction of geothermal energy 7 , and enhanced oil recovery 8 , 9 . Recent experimental studies have revealed that the multiphase flow properties (e.g., relative permeability and capillary pressure) of rocks are dependent on effective stress-induced pore deformation 10 12 . Mechanistically, multiphase flow mechanisms in porous rocks are expected to be stress-dependent as well, an idea that challenges the simplifying assumption of a static pore structure addressed in numerous studies associated with multiphase flow in porous media 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The physical mechanisms controlling stress-dependent pore deformations are well-understood, both analytically (based on poroelasticity theory 26 , 27 ), and experimentally 28 . These poromechanical interactions have been shown to have a major impact on single-phase (e.g., absolute permeability) and multiphase flow properties of porous media 10 12 . Hence, multiphase flow mechanisms including drainage (i.e., the wetting phase is displaced by the non-wetting phase) and imbibition (i.e., the non-wetting phase is displaced by the wetting phase) are also expected to be deformation-dependent in porous media.…”
Section: Introductionmentioning
confidence: 99%
“…Although diverse in methodology and material type, these experimental, analytical, and numerical studies have routinely treated the porous media as a stress-independent solid with zero solid-solid mechanical interaction. This restriction in the theoretical treatment persists despite the limited, but increasing, body of experimental 29–34 and analytical 35–37 evidence of changes to multiphase flow properties with effective stress-induced deformation. Complicated physical behaviors and contradictory findings continue to challenge our understanding of stress-dependent multiphase flow at pore-scale and core-scale 36,37 .…”
Section: Introductionmentioning
confidence: 99%